Penggunaan Istilah Binatang dalam Metafora Bahasa Indonesia dan Bahasa Mandarin - Laurencia, Noviana (Zenit, 2012)
Metaphor is a common thing we encounter in everyday language  use, because the metaphor is also a way of human thinking. Humans often use animal metaphors to define the appearance, behavior, character, or morals of a person. Basically, humans have thought the same concep to judge about something. However, because of the historical background, culture, customs and different environments, the introduction of something can be different, this causes a difference in the use of metaphor. This research uses contrastive analysis to show the similarities and differences of animal metaphors usages and their cultural meanings in Indonesian and Chinese languages.